PEMBERIAN WASIAT WAJIBAH KEPADA ANAK KANDUNG BERAGAMA BUDHA MENURUT HUKUM WARIS ISLAM INDONESIA (STUDI PUTUSAN NOMOR: 1763/PDT.G/2022/PA.JP): Granting A Mandatory Will To Buddhist Children According To Indonesian Islamic Heritage Law (Study Decision Number: 1763/Pdt.G/2022/Pa.Jp) - Kamila Ainul Hakim; Khairani Bakri (AMICUS CURIAE, 2025)
The inheritance process involves the transfer of assets from a deceased individual to their heirs, with Islamic inheritance law granting rights to children, surviving spouses, parents, and siblings based on the Ijbari principle. This research focuses on identification problem: the provision of obligatory bequest to Buddhist children under Indonesian Islamic inheritance law, and whether the ruling of Religious Court Number: 1763/Pdt.G/2022/PA.JP on this matter aligns with Indonesian Islamic inheritance law. The research employs a descriptive normative method using secondary data. Qualitative data analysis is conducted with conclusions drawn through deductive reasoning. The result and conclusion suggest that Indonesian Islamic inheritance law does not regulate the provision of obligatory bequests to non-Muslim children, including those of Buddhist faith, and that the Religious Court's decision is considered inconsistent with Article 209 KHI.